Filterable Agents for Hyperpolarization of Water, Metabolites, and Proteins. Issue 41 (22nd August 2016) - Vuichoud, Basile; Bornet, Aurélien; de Nanteuil, Florian; Milani, Jonas; Canet, Estel; Ji, Xiao; Miéville, Pascal; Weber, Emmanuelle; Kurzbach, Dennis; Flamm, Andrea; Konrat, Robert; Gossert, Alvar D.; et al.
Abstract: Hyperpolarization is generated by dissolution dynamic nuclear polarization (d‐DNP) using a polymer‐based polarizing agent dubbed FLAP (filterable labeled agents for polarization). It consists of a thermo‐responsive poly( N ‐isopropylacrylamide), also known as p NiPAM‐COOH, labeled with nitroxide radicals. The polymer powder is impregnated with an arbitrary solution of interest and frozen as is. Dissolution is followed by a simple filtration, leading to hyperpolarized solutions free from any contaminants. We demonstrated the use of FLAP to hyperpolarize partially deuterated water up to P ( 1 H)=6 % with a long relaxation T 1 >36 s characteristic of high purity. Water hyperpolarization can be transferred to drugs, metabolites, or proteins that are waiting in an NMR spectrometer, either by exchange of labile protons or through intermolecular Overhauser effects. We also show that FLAPs are suitable polarizing agents for 13 C‐labeled metabolites such as pyruvate, acetate, and alanine. Abstract : Partially deuterated water with T 1 (HDO) >36 s can be produced by dissolution dynamic nuclear polarization with a suspension of filterable labeled agents for polarization (FLAP) consisting of a thermo‐responsive poly( N ‐isopropylacrylamide) COOH‐terminated polymer ( p NIPAM‐COOH) tagged with nitroxide radicals. The resulting heterogeneous sample can be rapidly cooled to 1.2 K for dynamic nuclear polarization, and separated by filtration after rapid dissolution with superheated D2 O.